2015
DOI: 10.1049/iet-map.2014.0552
|View full text |Cite
|
Sign up to set email alerts
|

Design of millimetre wave diplexers with relaxed fabrication tolerances

Abstract: A novel millimetre wave waveguide diplexer topology that can be fabricated using relaxed fabrication tolerances is presented. This is achieved by using a highpass filter/hybrid coupler topology in addition to a low order capacitive iris bandpass filter. By targeting the most sensitive centre resonators in the bandpass filter and increasing their length to full wavelength, the sensitivity to fabrication errors associated with changes to the resonator length can be reduced without the introduction of spurious re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The in-band frequency response of the novel band-pass filters proposed in this paper is not based on coupled resonant structures as it happens in [17], [18] or in transmission lines of different characteristic impedances as it occurs in [20]. Instead, the passband characteristic has been realized by combining a reduced loss low-pass waveguide filter designed following the technique described in [6] and a high-pass configuration based on the cut-off effect [20].…”
Section: Novel Band-pass Filter Design Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The in-band frequency response of the novel band-pass filters proposed in this paper is not based on coupled resonant structures as it happens in [17], [18] or in transmission lines of different characteristic impedances as it occurs in [20]. Instead, the passband characteristic has been realized by combining a reduced loss low-pass waveguide filter designed following the technique described in [6] and a high-pass configuration based on the cut-off effect [20].…”
Section: Novel Band-pass Filter Design Proceduresmentioning
confidence: 99%
“…designing the filters to have sufficient margin to fulfill the frequency specifications at the cost of increasing the filter length, have been proposed in the literature [16]. In [17], the length of the resonating structures was enlarged to improve the tolerance issues. However, the latter implies that the overall size of the filter (and consequently the diplexer) increases as well and, besides, spurious resonances could appear below the passbands, which does not occur for half-wavelength resonators [18].…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate the translation process, a bandpass filter, highpass filter and hybrid coupler are designed using the method in [6] for use with RT 5880, which has a dielectric constant of 2.2 and a height 1.574 mm. Simulated results are shown in Figs.…”
Section: Design Of Siw Componentsmentioning
confidence: 99%
“…A recent circuit topology proposed by the authors has shown that the fabrication tolerance of millimetre wave diplexer circuits can be relaxed by using a hybrid coupler/highpass filter topology in addition to a bandpass filter with full wavelength centre resonators [5,6]. The main advantage of this topology is that the number of resonators in the diplexer circuit is halved when compared with other diplexers with a similar fractional bandwidth which relaxes the circuit sensitivity to fabrication errors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation